2015
DOI: 10.1177/2041669515599332
|View full text |Cite
|
Sign up to set email alerts
|

Policing Fish at Boston's Museum of Science: Studying Audiovisual Interaction in the Wild

Abstract: Boston's Museum of Science supports researchers whose projects advance science and provide educational opportunities to the Museum's visitors. For our project, 60 visitors to the Museum played “Fish Police!!,” a video game that examines audiovisual integration, including the ability to ignore irrelevant sensory information. Players, who ranged in age from 6 to 82 years, made speeded responses to computer-generated fish that swam rapidly across a tablet display. Responses were to be based solely on the rate (6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This smaller effect may have been caused by the relatively large difference between the oscillation frequencies used here (5 vs. 8 Hz). That large difference probably made the task easier than it had been with the 6 versus 8 Hz pair used by Goldberg et al. (2015).…”
Section: Results: Phasementioning
confidence: 99%
See 2 more Smart Citations
“…This smaller effect may have been caused by the relatively large difference between the oscillation frequencies used here (5 vs. 8 Hz). That large difference probably made the task easier than it had been with the 6 versus 8 Hz pair used by Goldberg et al. (2015).…”
Section: Results: Phasementioning
confidence: 99%
“…Note that the effect of congruence shown in the upper panel of Figure 1 is considerably smaller than the comparable effect from some previous studies with Fish Police!! (e.g., Goldberg et al., 2015). This smaller effect may have been caused by the relatively large difference between the oscillation frequencies used here (5 vs. 8 Hz).…”
Section: Results: Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies of multisensory temporal processing examined the influence of dynamic auditory stimuli on judgments of visual modulation rates in a multisensory scene offered by a video game (Fish Police! ; Goldberg et al, 2015;Sun et al, 2016). Players were asked to judge the rate at which a visual stimulus (a computer-generated fish) was modulated in size while it moved across the display and emitted an intensity-modulated sound.…”
Section: Introductionmentioning
confidence: 99%
“…These links include a suggestion that information from the two dimensions of processing converges at some site in the parietal lobe (e.g., Walsh 2003;Oliveri, Koch, & Caltagirone 2009). Such convergence might support a combination or coordination of temporal and spatial streams of information, as some psychophysical studies have shown (Goldberg et al, 2015;Keller & Sekuler, 2015). Although the tasks in those studies differed from ours, their results do suggest the possibility that by making both sources of information available at the same time, concurrent spatial and temporal presentations could enhance performance over what would be produced by either source alone.…”
Section: Resultsmentioning
confidence: 99%